Integrated development, risk management and community-based climate change adaptation in a mountain-plains system in Northern Tanzania - Elisabeth Edna Wangui; Thomas A. Smucker; Ben Wisner; Eric Lovell; Adolfo Mascarenhas; Maingi Solomon; Daniel Weiner; Abubakari Munna; Gaurav Sinha; Charles Bwenge; Hubert Meena; Pantaleo Munishi (Revue de Géographie Alpine)
This paper presents a preliminary analysis of work conducted along altitudinal gradients in the mountains and plains of northern Tanzania. We find evidence of a high degree of interdependence among groups of people of different language/cultural groups and socio-economic status interacting along environmental gradients from high to low altitude. We call this “socio-geographical adaptation” to climate change. However, our analysis and discussion adds complexity to any simple notion of “adaptation to climate change” since changes are multiple and adaptation is complex.